Feasibility Study of Criminalizing The Seller's Action in Mortgaging The Official Document of The Property Sold With an Ordinary Document - Somaye Noori; Mohammad Reza Kaykha; Ramin Faghani (پژوهشهای حقوقی, 2023)
An ordinary document or charter is a document whose purpose is to write a commitment and create a guarantee for the fulfillment of the obligation. One of the conceivable challenges related to the sale of real estate is the fact that after concluding a transaction with the preparation of an ordinary document, the seller, for various reasons, puts the official document of the same property as collateral, the main ambiguity of such an action is The feasibility aspect is the criminality of the seller's act; Because in this case there is no unity of procedure and the multiplicity of votes issued is evident. This article, which has been done in a descriptive-analytical method, while explaining the different aspects of the prying transaction from the crime of transferring other people's property and proving the ability of the ordinary document to oppose the official document, shows that He denies his possession in a prying manner, and according to the law of compulsory registration of documents, the time of compiling an ordinary document is a matter of concern, if the property did not have an official document at the time of sale and the seller Preparation of a formal official document, the subject can be subject to the provisions of Article 117 of the Registration Law based on the opposing transaction; However, the existence of an official document of the property during the transaction and its transfer by means of an ordinary document, causes the subject exclusion of the seller's act from the scope of Article 117 and consequently is considered as a crime of transferable property.